Role of Rehabilitation and Physical Therapy in Optimizing Outcomes after Joint Replacement Therapy - Shaukat Hayat Khan, Abdul Munaf Saud, Amir Hamza Khan, Luqman Asghar, Hisham Khan, Sijad Ahmed Mahar, Tauseef Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The objective of the current investigation was to evaluate the role of rehabilitation and physical therapy in optimizing outcomes after joint replacement therapy. Patients and Methods: This study retrospectively investigated 78 patients underwent joint replacement therapy in, Department of Orthopaedic Surgery, SKBZ/CMH Muzaffarabad, AJK March 2022 to April 2023. Patients of either gender aged 60-80 years, requiring unilateral total hip or knee arthroplasty for Osteoarthritis were included. Pre-operative physical therapy, option of anesthetic technique, early mobilization, reduction of urinary retention and catheterization, risk of deep vein thrombosis, and blood loss were the primary aspects of investigation. Length of stay (LOS), complication rate, and re-admission were primary outcomes. SPSS version 26 was used for data analysis. Results: Of the total 78 patients, the incidence of knee and hip joint replacement was 49 (62.8%) and 29 (37.2%), respectively. The overall mean age and LOS was 68.8±4.62 years and 4.2±1.7 days, respectively. About 73 (93.6%) patients had post-operative satisfaction (score >7). All the patients underwent joint replacement therapy were completely discharged, out of which physical therapy was continued complete autonomy, home-physiotherapist, and routine attendance in physiotherapy center in 46 (59%), 18 (23.1%), and 13 (16.9%), respectively. The prevalence of major complications was 10.3% (n=8). Conclusion: Rehabilitation and physical therapy enhanced the reduction in hospitalization stay, early patient’s discharge, and fast recovery to routine activities. Keywords: Joint replacement therapy, Rehabilitation, Physical therapy